Development and validation of the Parenteral Nutrition Impact Questionnaire (PNIQ), a patient-centric outcome measure for Home Parenteral Nutrition. Issue 3 (June 2018) - Wilburn, Jeanette; McKenna, Stephen P.; Heaney, Alice; Rouse, Matthew; Taylor, Michael; Culkin, Alison; Gabe, Simon; Burden, Sorrel; Lal, Simon
Summary: Background & aims: Patients with Type 3 Intestinal Failure (IF) who need Home Parenteral Nutrition (HPN) face several clinical, psychological and social problems. The study was designed to produce and test the first patient-centric measure for HPN ('PNIQ: Parenteral Nutrition Impact Questionnaire'). The new measure focused on the extent to which patients were able to fulfil their human needs. Methods: Questionnaire content was derived from the analysis of transcripts of interviews conducted with UK HPN patients. Cognitive debriefing interviews (CDIs) were performed to ensure patients found the draft scale clear, relevant and accessible. Finally, a test–-retest postal validation survey was conducted to reduce the number of items in the scale and to ensure that; it was unidimensional, reproducible and had construct validity. Results: The 30 interview transcripts were analysed to identify issues related to a wide range of needs. Fifteen CDIs showed that patients found the draft scale easy to complete and highly relevant. The postal survey included 233 patients on HPN recruited through two IF units. Items were rejected if they did not fit the Rasch model, had too similar content to other items or displayed differential item functioning related to age, gender or underlying mechanism of IF. A 20-item unidimensional scale was identified with high internal consistency (0.91) and test–retest reliability (0.92). Scores on PNIQ correlated moderately highly with social isolation, emotional reactions and energy level and were related to perceived interference on life of HPN. The underlying cause of IF did not influence the way the scale worked. Conclusions: The PNIQ is a scientifically rigorous, unidimensional outcome measure that provides a complete assessment of the effect of HPN on everyday life. It will prove useful for measuring patient value in clinical practice and for determining outcome in clinical trials, audit, economic evaluations and outcomes-based reimbursement.